Analysis and improvement proposal for greek yoghurt production in a peruvian company employing Lean tools (5S) - Lara Espinoza, Giancarlo (2023)
The purpose of this investigation was to apply the Lean 5S methodology to the Greek yoghurt production process of a Peruvian microenterprise with the aim of analyzing and propose improvements in order to promote a culture of continuous improvement. The methodology comprises the 5 stages of sort, set in order, shine, standardize and sustain. Several engineering tools were applied to this end, such as a process operations diagram, route diagram, time study, VSM and Load/Distance Matrix. The research achieved a reduction in production time, with indicators such as a 40 % reduction in the load-distance matrix, a 36,8 % reduction in travel time, a 64,4 % reduction in preparation time and an improved lead time by 21,52 %. In addition, productivity saw an increase of 65,94 % as well as 15 % higher production efficacy.